2022
DOI: 10.1111/jfpp.17255
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and nonthermal pretreatment methods for the extraction of anthocyanins: A review

Abstract: Functional plant bioactive such as polyphenols have drawn greater interest for researchers, food industries, and consumers. Anthocyanins are popular due to its high antioxidant activity and nutra‐pharmaceutical potential. As the demand for anthocyanins grows, exploring and acknowledging applications of various conventional and nonconventional means of anthocyanin extraction is important. Conventional extraction methods have some limitations in the context that these are most time‐consuming, tedious, and less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…Hence, an adequate balance between these two process factors is pivotal to achieve successful anthocyanin recovery. 34…”
Section: Resultsmentioning
confidence: 99%
“…Hence, an adequate balance between these two process factors is pivotal to achieve successful anthocyanin recovery. 34…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in agreement with Çoklar and Akbulut [ 51 ], who found that drying of black grapes using freeze-drying (−110 °C, 48 h) increased 16% of anthocyanins, but reduced 95% of these compounds in both oven- (60 °C, 17 h) and sun-dried (7 days) samples compared to fresh (~1752.94 mg/kg). Drying anthocyanins-rich plants will accelerate the extraction and allow penetration of solvent into cells and extract the targeted compounds while maintaining the chemical properties of anthocyanins [ 52 ]. Considering anthocyanins that are sensitive to light and heat, exposing the MP to direct sunlight for longer periods led to the degradation of heat-sensitive compounds, particularly anthocyanins.…”
Section: Resultsmentioning
confidence: 99%
“…As CM is low in Ca and acceptance, fortification in form of flavoring can be considered to achieve a good dairy alternative. To be more natural, additives from plant-based materials are desirable [112,113] . For example, certain vegetables such as Cosmos caudatus and water spinach contain an excellent amount of Ca and can easily be cultivated as they possess weed-like characteristics and grow in abundance [114] .…”
Section: Future Direction On Improving Cmbymentioning
confidence: 99%